Micromapping testicular sperm extraction: A new technique for microscopic testicular sperm extraction in nonobstructive azoospermia - Toshihiro Tai; Wakaba Miyamoto; Yuriko Fukuoka; Sena Shibasaki; Mizuho Takahashi; Noriyuki Okuyama; Hiromitsu Hattori; Ikue Ishikawa; Satoko Nagaura; Koki Yoshinaga; Masae Koizumi; Tomoko Hashimoto; et al. (Reproductive Medicine and Biology)
Abstract Purpose In microscopic testicular sperm extraction (mTESE) for nonobstructive azoospermia (NOA), sperm can be recovered relatively easily in some cases, and mTESE may be retrospectively considered excessive. However, mTESE is routinely performed in the majority of NOA patients because of the difficulty in predicting tissue status. A minimally invasive and comprehensive sperm retrieval method that allows on‐the‐spot tissue assessment is needed. We have developed and evaluated a novel sperm retrieval technique for NOA called micromapping testicular sperm extraction (MMTSE). Methods MMTSE involves dividing the testis into four sections and making multiple small needle holes in the tunica albuginea to extract seminiferous tubules and retrieve sperm. The sperm‐positive group by MMTSE (Group I) underwent additional tissue collection (ATC) via a small incision, whereas the sperm‐negative group by MMTSE (Group 0) underwent mTESE. Results In total, 40 NOA participants underwent MMTSE. Group I included 15 patients and Group 0 included 25 patients. In Group 1, sperm were recovered from all patients by ATC. In Group 0, sperm were recovered in 4 of 25 cases using mTESE. Conclusions MMTSE shows promise as a simple method that comprehensively searches testicular tissue and retrieves sperm using an appropriate method while minimizing patient burden.